USPORNI TURIZAM: TRŽIŠTE NIČA PREMA ODRŽIVOSTI KUĆE MJESECE FARME „BAROUK AREA“ - Hassan, Viana; Zrnić, Miloš (Turističko poslovanje, 2021)
Slow tourism is one of the new trending concepts that bring the concept of slowness into tourism practices in a way that tourists appreciate the local food, culture, heritage, and sustainability.Destinations adopting principles of slow tourism may reduce the financial leakage of the suppliers and generate more income and employment to the locals. Thus, the case of ” Moonlight farm and Resort at Barouk“ area, the core topic for this study to understand the relation between slow tourism sustainable development, ecology, which has the roots in interest for locality, community, and green travel.The main research question: “How can slow tourism be a tool of sustainable development?”. In order to answer this, a mixed-method approach conducted through the use of two questionnaires addressed to tourists visiting “Moonlight farm” and residents in Barouk area. Additionally, an interview with the owner would provide significant insight into the topic. The analysis of the results was beneficial in understanding the perceptions and motivations of tourists in which it helps promote slow tourism in this area.
Keywords: Barouk, Moonlight, spori turizam, održivi razvoj, nišno tržište